The renaissance of electrochemistry - Leidinger, Walter (2018)
Germany has decided to switch its entire energy supply to renewables in a transition that they have termed as “Energiewende”. A rethinking of industrial production, especially of the chemical production, is the consequence.Organic electrochemistry is thus celebrating a renaissance, since it allows the coupling of renewable energies and chemical production. A highly efficient, sustainable “green chemistry“ with CO2 as the future raw material basis is possible.